The Role of Stakeholders in Supporting the Implementation of Nagari Tageh in Tanah Datar Regency - Akmal, Artha Dini; Yuliarti, Yuliarti; Maani, Karjuni Dt; Permana, Iip; Agamuddin, Agri Americo (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
Nagari Tageh is a program implemented by the government to strengthen the community based on the community itself. Nagari Tageh is a reflection of the national program known as the Disaster Resilient Village. In West Sumatra, Nagari Tageh was initiated by the Regional Police (POLDA), and at the district level, it was carried out by the local police (POLRES). In Tanah Datar Regency, Nagari Tageh has been socialized since 2018, but there is still no Nagari that has been able to implement this program comprehensively. The involvement of other stakeholders that should support this program has also not been seen, as if the POLRES is working alone without cross-sectoral support. However, because the Nagari Tageh program is a strategic program that directly involves the Nagari community, contributions from other relevant agencies are urgently needed. This study aims to examine the roles that can be carried out by government institutions as stakeholders in the Nagari Tageh program so that it can be implemented more comprehensively in the future. This research uses a qualitative method with a descriptive approach. Data were collected through interviews with key informants from the Tanah Datar POLRES and several other stakeholders related to the Nagari Tageh program. The results show that stakeholders other than POLRES and the Nagari government actually have a commitment to support the implementation of Nagari Tageh, but there is no formal coordination or clear role division. Each institution has a different potential contribution according to its authority, but there is no binding collaboration mechanism. A coordinated structure between institutions is needed to ensure that this program can run in an integrated and sustainable manner.